BIOCHEMICAL CHANGES IN BEEF PATTIES BOILED WITH ETHANOL EXTRACT OF THE ROOT OF Glycyrrhiza glabra LINN (FUDMA JOURNAL OF SCIENCES, 2021)
The use of spices in boiling of meat is a common phenomenon. The root of Glycyrrhiza glabra is used locally as spice for met. This work was design to determine the effect of ethanol extract of Glycyrrhiza glabra on malondialdehyde content, percentage Metmyoglobin content, acid value, Heme-iron content and peroxide value of beef stored at 4oc for a storage time of 0 to 18 hours was evaluated. Samples were taken at interval of 6 hours for analysis of the biochemical parameters under study. The statistical difference observed in Acid value, Malondialdehyde content, Heme iron content and peroxide value showed no significant difference, all having P≥0.05 in beef treated with ethanol extract of Glycyrrhiza glabra when compared to the control. On the other hand, the statistical difference in percentage metmyoglobin content when compared to the control at 0 hour interval was significant having P≤0.05, then at other distinct time interval showed no significant difference having P≥0.05. Thus, this study revealed that the extract of Glycyrrhiza glabra have a decreased antioxidant property against rancidity in beef samples and peroxide formation, although the stability of antioxidant, antimicrobial properties of Glycyrrhiza glabra decreases with storage time resulting in the variation of percentage Metmyoglobin values, Malondialdehyde values and Heme iron values, Acid value and peroxide value of beef, which indicates it may not be a good spice for beef
Keywords: Spices; Glycyrrhiza glabra; malondialdehyde; metmyoglobin; acid value